2014
DOI: 10.1002/polb.23538
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and simulating morphology gradients in injection‐molded talc‐reinforced isotactic polypropylene

Abstract: Injection molded polymer parts are known to exhibit structural gradients of crystallinity, crystallite phases and crystallite orientations. The structural variations depend on the geometry, the material properties, and the processing conditions, and affect the mechanical properties of the molded part. We explore the use of raster‐scanning small‐ and wide‐angle X‐ray scattering (SAXS, WAXS) for mapping the microstructure in dogbone specimens of an isotactic polypropylene (PP) homopolymer and a talc‐reinforced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Healy et al utilized SAXS and WAXD to examine the residual chain orientation in microinjection‐molded linear polyethylene, and unraveled that it is the oriented crystal growth instead of residual chain orientation that contributes to the majority of the orientation. Granlund et al mapped the two‐dimensional (2D) chain orientation distribution in the cross‐section parallel and perpendicular to the flow direction in injection‐molded talc‐reinforced isotactic polypropylene using the raster scanning SAXS and WAXD, and indicated the structural heterogeneities and asymmetries as a result of lateral temperature gradient across the mold. Ulcer et al applied matrixing microbeam XRD and transmission optical photomicrographs to analyze the structure at the weld region of poly(arylene ether ketone), and revealed that the sample exhibits a multilayer structure at the weld line region.…”
Section: Introductionmentioning
confidence: 99%
“…Healy et al utilized SAXS and WAXD to examine the residual chain orientation in microinjection‐molded linear polyethylene, and unraveled that it is the oriented crystal growth instead of residual chain orientation that contributes to the majority of the orientation. Granlund et al mapped the two‐dimensional (2D) chain orientation distribution in the cross‐section parallel and perpendicular to the flow direction in injection‐molded talc‐reinforced isotactic polypropylene using the raster scanning SAXS and WAXD, and indicated the structural heterogeneities and asymmetries as a result of lateral temperature gradient across the mold. Ulcer et al applied matrixing microbeam XRD and transmission optical photomicrographs to analyze the structure at the weld region of poly(arylene ether ketone), and revealed that the sample exhibits a multilayer structure at the weld line region.…”
Section: Introductionmentioning
confidence: 99%
“…The sample used in this study was a specimen of injectionmoulded isotactic polypropylene (iPP) containing talc particles, chosen because we have previously performed raster scanning wide-and small-angle X-ray scattering of physically cut specimens of the same material (Granlund et al, 2013(Granlund et al, , 2014. The fact that the spatially resolved preferred orientation of the embedded talc flakes is known in advance makes it possible to compare the results from the SAXS-CT technique with the true orientation distribution.…”
Section: Methodsmentioning
confidence: 99%
“…For the reference raster scan experiment, a cross section of 1 mm thickness was physically cut, and the X-ray beam, being in this case parallel to the long axis of the original sample, was raster scanned in two dimensions along the x-and z-axis directions with a 15 mm step length, recording the scattering pattern at each position of the beam on the sample. Further experimental details regarding the sample material and preparation can be found in the paper by Granlund et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations